Contribution of Sheikh Abdul Wahab Rokan To The Internalization Of Moral Education in Besilam, Langkat Regency - Zailani, Zailani; Amalia, Isnaini (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The title of the research is the Contribution Analysis of Sheikh Abdul Wahab to the internalization of moral education in Besilam. Langkat Regency. The research formulation is what contribution Sheikh Abdul Wahab has made in moral education in Besilam, Langkat Regency and how relevant it is in Islamic life in Besilam, Langkat Regency. The purpose of this research is to analyze what contributions have been made by Sheikh Abdul Wahab Rokan to the internationalization of moral and relavance education in Islamic life in Besilam, Langkat Regency.This type of research is qualitative research. With a historical approach. The source of data used in this research is the library. This research is also called and field research. The data collection techniques in the field using the interview and observation methods. The results of this study indicate that Sheikh Abdul Wahab has an important contribution to the internalization of moral education in Besilam, starting from building a Mushola (Madrasah), Sheikh Abdul Wahab Rokan plays a role in determining the moral education curriculum in Besilam which emphasizes Tawhid and Tasawwuf and has relevance to Islamic life in Besilam, Langkat Regency.